Territory of Nebraska by Prof. H.D. Rogers & A. Keith Johnston F.R.S.E. - Rogers, H.D. (Cartographer); Johnston, A. Keith (Contributor)
Topographical map of Western North America, including territories of Utah, Oregon, Washington, Nebraska, Minnesota, and Iowa. Map area covers present day Idaho, Montana, Wyoming, North and South Dakota, and Colorado. Originally published in : Atlas of the United States of North America : Canada, New Brunswick, Nova Scotia, Newfoundland, Mexico, Central America, Cuba, and Jamaica. London : John Murray, 1857 Relief shown by hachures. Scale approximately 1:3,450,000 or 54.5 miles to 1 inch. Coloured markings show lines of municipal territories and a proposed railway. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .